2022
DOI: 10.3390/cancers14163947
|View full text |Cite
|
Sign up to set email alerts
|

Targeting MDM4 as a Novel Therapeutic Approach in Prostate Cancer Independent of p53 Status

Abstract: Metastatic prostate cancer is a lethal disease in patients incapable of responding to therapeutic interventions. Invasive prostate cancer spread is caused by failure of the normal anti-cancer defense systems that are controlled by the tumour suppressor protein, p53. Upon mutation, p53 malfunctions. Therapeutic strategies to directly re-empower the growth-restrictive capacities of p53 in cancers have largely been unsuccessful, frequently because of a failure to discriminate responses in diseased and healthy tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“… 59 Metastatic Prostate Cancer Whether p53 is mutated or not, overexpression of MDMX in prostate cancer is implicated in apoptosis or senescence. 75 Lung Cancer Non-Small Cell Lung Cancer High expression of MDMX is associated with poorly differentiated tumor cells, advanced TNM staging, and the occurrence of lymph node metastasis. 76 Non-Small Cell Lung Cancer Overexpression of MDMX affects prognosis in NSCLC patients, which is associated with MDMX regulation of NSCLC cell proliferation and chemotherapy sensitivity.…”
Section: Phosphorylationmentioning
confidence: 99%
“… 59 Metastatic Prostate Cancer Whether p53 is mutated or not, overexpression of MDMX in prostate cancer is implicated in apoptosis or senescence. 75 Lung Cancer Non-Small Cell Lung Cancer High expression of MDMX is associated with poorly differentiated tumor cells, advanced TNM staging, and the occurrence of lymph node metastasis. 76 Non-Small Cell Lung Cancer Overexpression of MDMX affects prognosis in NSCLC patients, which is associated with MDMX regulation of NSCLC cell proliferation and chemotherapy sensitivity.…”
Section: Phosphorylationmentioning
confidence: 99%
“…Previous studies have reported that MDM4 can promote endogenous apoptosis by regulating the expression of oncogene p53 and that USP2a can interact with MDM4 to inhibit its ubiquitin-mediated degradation ( 91 , 136 , 137 ). The expression of MDM4 and USP2a is significantly lower in GBM tissues than in normal brain tissues and is positively associated with the prognosis of GBM; that is, the higher the expression, the more improved the prognosis.…”
Section: Targeting Usp2 For Cancer Therapymentioning
confidence: 99%
“…We identify edges that are most enriched in our GWAS+ cluster which could be pointing to essential links between the gene encoding for the node and containing a PrCa predisposing SNP at a particular EPIN. For example, we identify the link between MDM4 containing SNP rs35946963 (PrCa p-value 1e−24) and TP53 37 and between KDM2A containing SNP rs12790261 (PrCa p-value 1e−7) and BCL6 38 and ARNT continuing SNP rs139885151 (PrCa p-value 3e−13) and HIF1A 39 .…”
Section: Articlementioning
confidence: 99%